Impact of Sickle Hemoglobinopathies on Pregnancy-Related Venous Thromboembolism - Porter, Blake; Key, Nigel S.; Jauk, Victoria Chapman; Adam, Soheir; Biggio, Joseph; Tita, Alan (American Journal of Perinatology, 2014)
Objective The aim of the study is to examine the relationship between sickle cell trait (Hb AS) and other sickle hemoglobinopathies and the risk of thromboembolism during pregnancy or the puerperium.Study Design Retrospective cohort study of African American women receiving prenatal care from 1991 to 2006. Sickle cell status was ascertained by routine hemoglobin electrophoresis. Venous thromboembolism (VTE) was defined as one or more episodes of deep venous and/or pulmonary thromboembolism during pregnancy or the puerperium according to discharge diagnoses based on International Classification of Diseases, Ninth Revision codes.Results Among 22,140 women with hemoglobin (Hb) AA status, 20 women (0.09%) experienced pregnancy-related VTE compared with 3 women (0.15%) of 2,037 women with Hb AS; relative risk (RR) for the association with AS status = 1.6; 95% confidence interval (CI) 0.5 to 5.5. Of 103 women, 3 women (2.9%) with sickle cell disease conditions (Hb SS, Hb SC, or Hb S,beta-thalassemia) experienced thromboembolism. Compared with women with Hb AA status, the RR = 32.2, 95% CI 9.7 to 107.Conclusion Sickle cell trait may be associated with a modest increase in VTE in the setting of pregnancy; sickle cell disease conditions are strongly associated with this rare but potentially fatal outcome.
Keywords: sickle cell disease; sickle cell trait; venous thromboembolism; pregnancy